Comparison of long-term survival of patients with BCLC stage B hepatocellular carcinoma after liver resection or transarterial chemoembolization. - Jian-Hong Zhong (Public Library of Science (PLoS), 2013)
Background and aims Treatment of patients with Barcelona Clinic Liver Cancer Stage B hepatocellular carcinoma (BCLC-B HCC) is controversial. This study compared the long-term survival of patients with BCLC-B HCC who received liver resection (LR) or transarterial chemoembolization (TACE). Methods A total of 257 and 135 BCLC-B HCC patients undergoing LR and TACE, respectively, were retrospectively evaluated. Kaplan-Meier method was used for long-term survival analysis. Independent prognostic predictors were determined by the Cox proportional hazards model. Results The hospital mortality rate was similar between groups (3.1% vs. 3.7%; P = 0.76). However, the LR group showed a significantly higher postoperative complication rate than the TACE group (28 vs. 18.5%; P = 0.04). At the same time, the LR group showed significantly higher overall survival rates (1 year, 84 vs. 69%; 3 years, 59 vs. 29%; 5 years, 37 vs. 14%; P<0.001). Moreover, similar results were observed in the propensity score model. Three independent prognostic factors were associated with worse overall survival: serum AFP level (≥400 ng/ml), serum ALT level, and TACE. Conclusions LR appears to be as safe as TACE for patients with BCLC-B HCC, and it provides better long-term overall survival. However, prospective studies are needed to disclose if LR may be regarded as the preferred treatment for these patients as long as liver function is preserved.